2011
DOI: 10.1080/21507716.2011.631514
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Psychiatric Research: A Review of 25 Years of NIH-Funded Empirical Research Projects

Abstract: Background This paper reviews the past 25 years of empirical research funded by the National Institutes of Health (NIH) on matters of ethics in psychiatric research. Methods Using the NIH RePORTER and Medline databases, we identified 43 grants and 77 publications that involved the empirical study of a matter of ethics in research involving mental health service users. Results These articles provide original and useful information on important topics, most especially the capacity to consent and the voluntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 99 publications
(101 reference statements)
1
13
0
Order By: Relevance
“…Three key points emerge from these results. First, congruent with existing literature from HICs [ 5 , 17 ] our findings support the growing evidence demonstrating the ability to improve decisional capacity through an iterative learning process using the UBACC. The UBACC proved an effective tool for improving understanding of SAX research study elements during recruitment of both cases and controls in our LMIC setting.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Three key points emerge from these results. First, congruent with existing literature from HICs [ 5 , 17 ] our findings support the growing evidence demonstrating the ability to improve decisional capacity through an iterative learning process using the UBACC. The UBACC proved an effective tool for improving understanding of SAX research study elements during recruitment of both cases and controls in our LMIC setting.…”
Section: Discussionsupporting
confidence: 87%
“…Studies in HICs show that understanding of informed consent materials can be improved through an iterative learning process of firstly presenting the study information, secondly assessing a participant’s understanding of the study elements, and finally revisiting and revising poorly understood elements [ 5 7 ]. Participant understanding has been shown to be reliably assessed using the University of California, San Diego Brief Assessment of Capacity to Consent Questionnaire (UBACC), which was originally developed as a 10-item screening tool for decisional capacity in participants being recruited for schizophrenia research [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that use of a simplified consent form—one using figures and plain language—can improve understanding (Dunn & Jeste, 2001; Kim & Kim, 2015). Others have found that an iterative process of assessing understanding, identifying areas of misunderstanding, and providing corrective feedback can lead to significant improvements in the understanding and appreciation of information (DuBois, Bante, & Hadley, 2011; Nishimura et al, 2013). However, as cognitive impairments grow more severe, such an approach may be inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mental health consumers tend to prioritize more than researchers a focus on alternative treatment modalities (such as nutritional or self-help modalities), iatrogenic harms, and qualitative research. 99,100 …”
Section: Introductionmentioning
confidence: 99%